2022
DOI: 10.1007/s00432-022-04465-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, prognostic, and immunological roles of CD177 in cervical cancer

Abstract: Background.CD177, an indicator of prognosis in diverse cancers, is involved in the physiological processes of various tumor cells, and acts as an immune molecule with novel functions in cancer pathogenesis. However, the diagnostic, prognostic and immunological role of CD177 in cervical cancer remains unclear. Methods.Utilizing publicly available databases and integrating several bioinformatics analysis methods, we evaluated the expression level of CD177 in cervical cancer by GENT2, HPA and GEO databases. The K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a recent publication, the high CD177 levels discriminated against non‐survivors patients with COVID‐19 [32]. Also, in ovarian cancer, CD177 expression on tumour tissue is related to tumour malignancy and a bad prognosis [33], while in breast and cervical cancers, it is related to shorter overall survival [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication, the high CD177 levels discriminated against non‐survivors patients with COVID‐19 [32]. Also, in ovarian cancer, CD177 expression on tumour tissue is related to tumour malignancy and a bad prognosis [33], while in breast and cervical cancers, it is related to shorter overall survival [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…In the eld of cancer, CD177 is considered to be a doubleedged role in afecting the clinical remarkable and prognosis value in variety cancer. Overexpression of CD177 importantly association with awful outcome in ovarian and pancreatic ductal adenocarcinoma but association with a excellent outcome in breast cance [9] [10]. Importantly, currently research has demonstrated that CD177 could improve the inhibitory function of tumor-in trating Treg cells (TC) in the TME, and blocking CD177 with antibodies in CD177 + tumor-in trating cells may be a novel target for antitumor immunotherapy [11].…”
Section: Introductionmentioning
confidence: 99%